Bibliography on Cold Regions Science and Technology, Volume XXV, Part 2. - COLD REGIONS RESEARCH AND ENGINEERING LAB HANOVER N H (1971)
The report is a companion issue to CRREL Report 12, Vol. XXV, Pt. 1 and contains the author and subject indexes. (Author) See also Volume 25, Part 1, AD-740 201.